The politics of economic nationalism in Japan: backlash against inward foreign direct investment? - Suginohara, Masako (2008)
This paper examines whether increased presence of foreign capital has led to the spread of economic nationalism in Japan and whether such nationalism has affected economic policy making. The study finds the general public has not embraced nationalistic assertions, while some policymakers had attempted to use nationalism to realize their favored policies. - Reproduced.
Keywords: Foreign investment